Understanding sexual and reproductive health needs of adolescents: evidence from a formative evaluation in Wakiso district, Uganda - Atuyambe, Lynn M.; Kibira, Simon P S; Bukenya, Justine (Reproductive health, 2015)
Adolescents are frequently reluctant to seek sexual and reproductive health services (SRH). In Uganda, adolescent health and development is constrained by translation of the relevant policies to practice. Recent studies done in central Uganda have shown that there is need for a critical assessment of adolescent friendly services (AFS) to gain insights on current practice and inform future interventions. This study aimed to assess the sexual reproductive health needs of the adolescents and explored their attitudes towards current services available.
Keywords: Adolescent, Sexual, Reproductive health, Needs, Uganda